Transformation of the MSME Digital Economy: An Inclusive Financial Management Strategy in Indonesia Towards a Global Market - Solikhah, Mar'atus (Journal of Management Economic and Financial, 2025)
Digital economy transformation has become one of the key factors in encouraging the sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia. As a contributor to more than 60% of GDP, MSMEs face the challenge of adapting to digitalization, especially in inclusive financial management. This research aims to: (1) analyze the readiness of MSMEs to adopt digital-based financial management, (2) identify effective strategies to increase global competitiveness, and (3) develop a conceptual framework for the transformation of the MSME digital economy towards the international market. The research method uses a mixed methods approach, with quantitative data collection through surveys of 300 MSMEs in four regions of Indonesia, as well as qualitative data through in-depth interviews with 30 MSME actors and stakeholders. Quantitative analysis was carried out using Structural Equation Modeling (SEM), while qualitative data was analyzed through thematic analysis. The results showed that digital readiness had a significant effect on inclusive financial management with a path coefficient of 0.65 (p < 0.01), and inclusive financial management contributed to an increase in operational efficiency of up to 38%. In addition, the integration of digital technology encourages the acceleration of transactions and global market access. The qualitative findings confirm that MSMEs that adopt digital financial applications are better able to expand international networks through e-commerce platforms. This study emphasizes that policy interventions, digital financial literacy, and access to inclusive services are key factors in strengthening the global competitiveness of Indonesian MSMEs.